Jianjue zhichi Yazhou Feizhou Lading Meizhou renminde fandi douzheng - Zhou Ruizhuang,
'Vigorously support the anti-imperialist struggle of the peoples of Asia, Africa and Latin America'. 2 cop.: resp. in Chinese and western languages; in different colours. Size of BG E3/725: 53.5x77.5 cm. See also BG E13/800.